2014
DOI: 10.1089/end.2013.0704
|View full text |Cite
|
Sign up to set email alerts
|

Anderson-Hynes Pyeloplasty in Patients Less Than 12 Months Old. Is the Laparoscopic Approach Safe and Feasible?

Abstract: The laparoscopic approach of Anderson-Hynes pyeloplasty in patients less than 12 months old is a safe procedure with the same outcomes as the open approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…Although there are some reported series of LP in infants with minimal complications ( 11 , 12 ); in other series, stent reported complications have ranged between 10 ( 1 ) and 35% of cases ( 13 ). Some authors reported acceptable results with unstented LP in selected cases ( 14 ) but others have published unfavorable results when no stents were used ( 15 ).…”
Section: Discussionmentioning
confidence: 96%
“…Although there are some reported series of LP in infants with minimal complications ( 11 , 12 ); in other series, stent reported complications have ranged between 10 ( 1 ) and 35% of cases ( 13 ). Some authors reported acceptable results with unstented LP in selected cases ( 14 ) but others have published unfavorable results when no stents were used ( 15 ).…”
Section: Discussionmentioning
confidence: 96%
“…In 2012, if the cut-off had been 10 kg (1 year old), 12 laparoscopic nephrectomies and 20 pyeloplasties could have been performed. This cut-off appears to be feasible both technically and in terms of anaesthesia [16]. With the introduction of robotic MIS, this goal might even be easier to accomplish [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan çalışma-larda, ortalama kalış süresi 3,24 gün olarak belirtilmektedir. 12,13 Hastalarımızın hastanede kalış süresi ortalama 3,59 gün'dür.…”
Section: Discussionunclassified